N6‐Methyladenosine detected in RNA of testicular germ cell tumors is controlled by METTL3, ALKBH5, YTHDC1/F1/F2, and HNRNPC as writers, erasers, and readers. (23rd March 2019) - Nettersheim, D.; Berger, D.; Jostes, S.; Kristiansen, G.; Lochnit, G.; Schorle, H.
Abstract: Background: Type II testicular germ cell tumors (GCTs) arise from a common precursor lesion (germ cell neoplasia in situ) and are stratified into seminomas and non‐seminomas, which differ considerably in morphology, gene expression, and epigenetic landscape. The N6‐methyladenosine (6mA) epigenetic modification is the most abundant modification in mRNA and is also detectable in eukaryotic DNA. The functional role of 6mA is not fully understood, but 6mA residues may influence transcription by affecting splicing, miRNA processing, and mRNA stability. Additionally, the methyl group of 6mA destabilizes Watson–Crick base‐pairing affecting RNA structure and protein binding. Objectives: Here, we analyzed the presence of the 6mA epigenetic modification in germ cells and GCT tissues and cell lines. Materials and methods: We screened for the presence of 6mA in DNA and RNA by immunohistochemistry, mass spectrometry or ELISA‐based quantification assays. Additionally, expression of 6mA writer‐, eraser‐ and reader‐factors was analyzed by microarrays, qRT‐PCR, western blotting and screening of public databases. Results: We demonstrate that 6mA is detectable in RNA, but not DNA, of GCT cell lines and tissues, fibroblasts, and Sertoli cells as well as germ cells of different developmental stages. Based on expression analyses, our results suggest METTL3, ALKBH5, YTHDC1, YTHDF1, YTHDF2 and HNRNPC as main writers, erasers, and readers of the 6mA modification in GCTs. Discussion: Owing to the lack of 6mA in DNA of GCTs, a functional role in regulating DNA transcription can be excluded. Interestingly, expression levels of 6mA regulators are comparable between tumor and normal tissues/cells, suggesting a similar mechanism of 6mA regulation in RNA. Finally, we demonstrate that 6mA levels in RNA increase upon differentiation of GCT cell lines, suggesting a role of 6mA in cell fate decisions. Conclusion: In summary, our data provide the starting point for further experiments deciphering the role of 6mA in the RNA of GCTs.